Strategi Edukasi dan Promosi Kesehatan untuk Optimalisasi Pencegahan Komplikasi Diabetes Mellitus dan Hipertensi pada Usia Remaja - Defi Nurul Hayati; Jannatin Nur Aripin; Muhammad Ramadhani Suryolaksono; Kurnia Ritma Dhanti; Syaukaty Yasinta; Rosi Wulandari; Albert Febrian Zebina Guevara; Rifka Utami (Forum Kerjasama Pendidikan Tinggi, 2025)
Hypertension and diabetes mellitus are non-communicable diseases with a steadily increasing prevalence, including among adolescents. Lack of knowledge and unhealthy lifestyles are the main risk factors. Based on this, this community service activity aimed to improve students’ knowledge at SMA Muhammadiyah 1 Purbalingga regarding both diseases and to conduct health screening as an early detection effort. The method included health education using PowerPoint media, preceded by a pre-test and followed by a post-test to assess knowledge improvement. In addition, random blood glucose tests and blood pressure measurements were carried out as part of the health screening. The results showed a significant increase in students' knowledge after the educational session (p < 0.05), and several students were found to have abnormal blood glucose and blood pressure levels. This activity demonstrated that health education and screening are effective in raising students' awareness of the importance of preventing non-communicable diseases. These findings highlight the need for continuous education and the adoption of a healthy lifestyle from an early age to prevent future complications.